2016
DOI: 10.3389/fpubh.2016.00134
|View full text |Cite
|
Sign up to set email alerts
|

Upper Limb Muscle Activity among Workers in Large-Herd Industrialized Dairy Operations

Abstract: ObjectivesThe primary aim of this cross-sectional research study was to quantify upper limb muscle activity among workers performing milking tasks in large-herd dairy parlors.MethodsSurface electromyography (sEMG) from the trapezius, anterior deltoid, biceps brachii, wrist flexors, and wrist extensors muscles of 26 dairy workers were used to create muscle activity profiles for the milking tasks common in large-herd dairy parlors. Functional maximum voluntary contractions (fMVC) were collected to normalize the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Limitations of our study design relate to our measurement method, as well as selection and timing of exercises. Indeed, skin surface EMG recordings may be affected by cross talk from nearby muscle groups . The time assigned to perform the exercises in this study (3 min) is much less than the average duration of surgery and our results may therefore underestimate the upper extremity workload experienced by surgeons in the clinical setting.…”
Section: Discussionmentioning
confidence: 84%
“…Limitations of our study design relate to our measurement method, as well as selection and timing of exercises. Indeed, skin surface EMG recordings may be affected by cross talk from nearby muscle groups . The time assigned to perform the exercises in this study (3 min) is much less than the average duration of surgery and our results may therefore underestimate the upper extremity workload experienced by surgeons in the clinical setting.…”
Section: Discussionmentioning
confidence: 84%
“…Some studies, instead, directly measure when FSE are found. Most of the studies reported that fatigue is found in industrial tasks in working places [ 150 , 167 ] but also in simulated environments [ 29 , 32 ]. In a limited number of studies, the effects of FSE were not observed or they were under the limit for high risk of MSD development [ 117 , 136 ].…”
Section: Resultsmentioning
confidence: 99%
“…The largest category consisted of papers that assessed the risk of MSD development, identifying most of the working activities as having a high risk, since the FSE exceeded the recommended threshold limits. These assessments were performed mainly with scales and questionnaires [ 193 , 202 ], but in some cases also kinematics and EMG signals were used [ 135 , 167 ]. Very few studies did not find FSE in the working tasks [ 117 , 136 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anthropometric measurements were recorded from all subjects in both the U.S. and Italian research sites, according to methods described by Rodgers ( 28 ) and Mixco et al ( 29 ). These measurements included functional overhead reach, functional standing height (wearing shoes), shoulder acromial height, forward functional reach, and grip breadth, which were measured as the circumference between the thumb and middle finger.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…These measurements included functional overhead reach, functional standing height (wearing shoes), shoulder acromial height, forward functional reach, and grip breadth, which were measured as the circumference between the thumb and middle finger. In both the countries, surface electromyography (sEMG) with a sampling frequency of 1,000 Hz using Biometrics DataLOG (Biometrics, England) was collected from the upper trapezius, anterior deltoid, biceps brachii, wrist flexors, and wrist extensors as described in detail previously ( 29 ). At the U.S. dairy farms, data were recorded for the length of time it took to completely milk a pen of cows (range of 225–275 cows), approximately 45–90 min.…”
Section: Methods and Proceduresmentioning
confidence: 99%